26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0209
|View full text |Cite
|
Sign up to set email alerts
|

Towards Facility Management Participation in Design: A UCSF Case Study

Abstract: The discipline of Facility Management (FM) emerged in the 1970s triggered by the concomitance of (1) increasing complexity in the workplace and (2) understanding of an interdependence between users' behaviors and building design. Despite the existence of FM, a number of buildings today still fail to deliver value during the occupation phase. Although various causes contribute to such failures, this paper focuses on the lack of strategic involvement of Facilities Managers (FMs) in design. It uses the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…FM professionals can provide cost effective recommendations when selecting supporting infrastructure. The recommendations may include methods in which the architects and engineers can integrate sustainable designs and systems to decrease costs over the project life cycle (Bascoul 2018;Pilanawithana and Sandanayake 2017). Integrating the FM professional provides the added long-term benefit of building in maintainability and sustainability (building in quality)with respects to customer needsmust be considered from concept through design.…”
Section: Fm In Programming and Design (Pd)mentioning
confidence: 99%
“…FM professionals can provide cost effective recommendations when selecting supporting infrastructure. The recommendations may include methods in which the architects and engineers can integrate sustainable designs and systems to decrease costs over the project life cycle (Bascoul 2018;Pilanawithana and Sandanayake 2017). Integrating the FM professional provides the added long-term benefit of building in maintainability and sustainability (building in quality)with respects to customer needsmust be considered from concept through design.…”
Section: Fm In Programming and Design (Pd)mentioning
confidence: 99%
“…The solution to this, according to Terreno et al (2019), is to apply the lean concept in the implementation of BIM in FM. Likewise, Bascoul et al (2018) suggested the adoption of lean practice should considering FM requirements early in the design process which allows the project team to understand the complexity of the programs housed by a facility prior to the building commissioning. Umstot et al ’s (2014) study is supported by empirical evidence showing public agencies can greatly benefit from lean principles and practices in ongoing maintenance of capital assets.…”
Section: Connecting Lean Management Principles To Facilities Managementmentioning
confidence: 99%
“…Facility Management was established to operate and manage the building upon delivery by the Design and Construction team, providing value to the client for several years after delivery (Bascoul, Tommelein, Tillmann and Muxen, 2018). Building Information Modeling(BIM) is an important factor in improving decision making for buildings throughout their life cycle to eliminates waste and rework in a collaborative flow.…”
Section: Literature Reviewmentioning
confidence: 99%